Pengaruh Prosedur Pembiayaan, Kualitas Pelayanan dan Tingkat Bagi Hasil terhadap Keputusan Pengambilan Pembiayaan Mudharabah pada Bank Syariah Indonesia Jambi - Firman Hidayat (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2023)
This article is entitled The Influence of Financing Procedures, Quality of Service and Profit Sharing Levels on Decisions to Take Mudharabah Financing at Bank Syariah Indonesia Jambi. The purpose of this study was to determine the effect of financing procedures, service quality, and profit-sharing rates on the decision to take mudharabah financing at Jambi Syariah Bank. This research approach is a qualitative research method based on data obtained from the company, both from questionnaires, interviews, observation and documentation as a support for analyzing the data. Based on the data and discussion that has been carried out and presented, it can be concluded with a number of points as follows: a) Financing procedures have a significant effect on mudharabah financing decisions at Indonesian Sharia banks (Bsi) Area because the calculated t value in the financing procedure variable (X1) is equal to 2.136 with a significant level of 0.005; b) Service Quality has a significant effect on the decision on mudharabah financing at Indonesian Sharia banks (Bsi) Area because the calculated t value for the service quality variable (X2) is 3.939 with a significant level of 0.005; c) The level of profit sharing has a significant effect on the decision on mudharabah financing at Bank Syariah Indonesia (Bsi) Area because the calculated t value for the profit sharing rate variable (X3) is 3.733 with a significant level of 0.005 and; d) Based on the results of simultaneous testing of the financing procedure variable (X1), service quality (X2) and profit sharing rate (X3) together have a significant effect on the decision (Y) because the F table value is 2.71, then the calculated F value (53.628) > F table (2.71) and significant value (0.000) < ? (0.05), then Ho is rejected and Ha is accepted.